The Effectiveness of Cognitive Behavioral Counseling with Bibliocounseling Techniques to Improve the Respectful Mind of Junior High School Students - Lestari, Luh Putu Sri; Hidayah, Nur; Ramli, M.; Lasan, Blasius Boli; Dharmayanti , Putu Ari (Universitas Pendidikan Ganesha, 2023)
Nowadays in junior high school there are students who show behavior that indicates a low respectful mind. In improving respectful mind of junior high school students is needed suitable technique in counseling, bibliocounseling techniques is one of suitable technique. This study aims to test the effectiveness of cognitive behavioral counseling with bibliocounseling techniques to improve the respectful mind of junior high school students. This study used a type of quasi-experimental design research using nonequivalent control group design. The sampling technique in this study is using a simple random sampling technique. The data analysis technique used in this study is through two ways, namely nonparametric statistical test, and Wilcoxon test conducted with the help of the SPSS for windows program version 25.00. The calculation results of the Wilcoxon signed rank test in table 4.12 show a Z value obtained of -2.524 with a p value (Asymp. Sig. 2-tailed) of 0.012 which is less than the critical limit of the study which is 0.05, this means that there is a difference between the pretest and posttest results in the respectful mind of students. Furthermore the paired t-test calculation results show a Sig. (2-tailed) value of 0.000 (p < 0.05). It can be concluded that there is a significant difference in students’ respectful minds after being given treatment.